Severe Enoral Bleeding with a Direct Oral Anticoagulant after Tooth Extraction and Heparin Bridging Treatment. (29th October 2019) - Ehrhard, Simone; Burkhard, John Patrik; Exadaktylos, Aristomenis K.; Sauter, Thomas C.
Abstract : Background . The number of patients receiving direct oral anticoagulants (DOACs) is increasing, however, this treatment is associated with the risk of bleeding. More than 10 percent of patients on DOACs have to interrupt their anticoagulation for an invasive procedure every year. For this reason, the correct management of DOACs in the perioperative setting is mandatory. Case Presentation . An 81-year-old male patient, with known impaired renal function, presented to our emergency department with a severe enoral bleeding after tooth extraction. The DOAC therapy—indicated by known atrial fibrillation—was interrupted perioperatively and bridged with Low Molecular Weight Heparin (LMWH). The acute bleeding was stopped by local surgery. The factors contributing to the bleeding complication were bridging of DOAC treatment, together with prolonged drug action in chronic kidney disease. Conclusion . In order to decide whether it is necessary to stop DOAC medication for tooth extraction, it is important to carefully weigh up the individual risks of bleeding and thrombosis. If DOAC therapy is interrupted, bridging should be reserved for thromboembolic high-risk situations. Particular caution is required in patients with impaired kidney function, due to the risk of accumulation and prolonged anticoagulant effect of both DOACs and LMWH.